Pendidikan Masyarakat Pandean Perspektif Nyadran - Sumarno Sumarno (Proceedings of Annual Conference for Muslim Scholars, 2018)
Education is the conscious efforts made by society to change for better. Nyadran is a tradition that exists in societies that have values education so need to kept and preserved. Nyadran is defined as well as the tradition of the community in the form of habit tribute to decreased ancestors with the pilgrimage through the Tomb that was done ahead of the fasting month in order to cleanse the liver. This research aims to uncover the facts against the value of existing community education through nyadran. In this study the author uses qualitative approach method of descriptive for this means that the data collected comes from the results of the interviews, field notes and documentation. As for the value and purpose in nyadran in the village of Pandean is; first, keeping local traditions already sustainably; second, maintaining an attitude of mutual cooperation or in the community; third, give each other and help your fellow community; fourth, rid yourself of that nature is not good; fifth, ask for help and a blessing on the ghosts of ancestors; sixth, respect and maintain the tombs of ancestors who have died.